Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1103/physrevc.91.044318
|View full text |Cite
|
Sign up to set email alerts
|

Pygmy resonances and radiative nucleon captures for stellar nucleosynthesis

Abstract: The impact of low-energy multipole excitations and pygmy resonances on radiative neutron and proton-capture cross sections in nuclei close to the β-stability line is investigated. For this purpose, a microscopic theoretical approach based on self-consistent density functional theory and quasiparticle-random-phase-approximation formalism extended with multiphonon degrees of freedom is implemented in a statistical reaction model. The advantage of the method is the microscopic nuclear structure input for unified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 58 publications
(141 reference statements)
5
92
0
Order By: Relevance
“…These include the low-energy tail of the IVGDR, PDR [18,19,27,28], multi-phonon excitations [19,29], toroidal modes [23] and α-cluster vibrations [30,31]. Furthermore, in recent studies it has been pointed out that the interaction between quasiparticles and phonons is important for a correct theoretical description of the low-lying E1 strength because it can influence its fragmentation and mixing with the core polarization and the IVGDR [18,19,29,[32][33][34][35]. This affects strongly the electromagnetic strength distribution, which can have further consequences on the dipole polarizability and nucleosynthesis processes [29,34,36].…”
Section: Introductionmentioning
confidence: 99%
“…These include the low-energy tail of the IVGDR, PDR [18,19,27,28], multi-phonon excitations [19,29], toroidal modes [23] and α-cluster vibrations [30,31]. Furthermore, in recent studies it has been pointed out that the interaction between quasiparticles and phonons is important for a correct theoretical description of the low-lying E1 strength because it can influence its fragmentation and mixing with the core polarization and the IVGDR [18,19,29,[32][33][34][35]. This affects strongly the electromagnetic strength distribution, which can have further consequences on the dipole polarizability and nucleosynthesis processes [29,34,36].…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by solving the groundstate problem in a semi-microscopic approach based on a Skyrme energy density functional (EDF) [26,27]. The EDF+QPM calculations have been applied for calculating the low-energy dipole strength [26,27], as well as used for astrophysical applications [28]. The results indicate that the radiative capture cross sections are underestimated by a factor of about two by the QRPA for the N = 50 nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The QPM results have recently applied very successfully in astrophysical investigations [12,23]. The model as used for beta-stable and unstable nuclei is found to provide a nearly perfect description of astrophysical reaction rates, much better than the widely used QRPA approach which, in fact, should be considered as a first order approximation.…”
Section: New Modes Of Excitation In Charge-asymmetric Nucleimentioning
confidence: 99%
“…In recent years nuclear density functional theory and nuclear many-body methods -ranging from HFB and (Q)RPA theory to the QPM approach of Soloviev et al -have been used to study systematically ground state properties and multipole response functions of exotic nuclei, especially in the region of the N = 82 and the Z = 50 shell closures, see e.g. [1] and detailed studies are found in [2][3][4][5][6][7][8][9][10][11][12][13][14]. None of those systems can be explored without an adequate reaction theory.…”
Section: Introductionmentioning
confidence: 99%